The threshold impact of interest rates on economic growth: Empirical evidence from panel data - Min-Joon Kim (Global Business & Finance Review (GBFR), 2024)
Purpose: The symmetric relationship between interest rates and economic growth had been explored in many em-pirical studies using various econometric techniques. However, the asymmetric relationship between them was still limited because it had not been thoroughly examined. This paper sheds light on the asymmetric impact of interest rates on economic growth using a panel threshold (PTR) model. Design/methodology/approach: Using the PTR model allowed us to accurately determine the threshold value of the interest rate and its impact on economic growth at each critical level. Data from 34 developing economies for the period 1992-2022 were analysed for this study. Findings: Experimental results showed that interest rates less than or equal to 5.286% promoted economic growth. In the opposite context, interest rates caused overall economic growth to decline. Research limitations/implications: The limitation of this study was that it did not consider the threshold effect of interest rates in individual country contexts. Furthermore, the empirical model only analyzed the impact of nomi-nal interest rates and did not consider real interest rates. Therefore, future research will benefit from expanding its scope as well as examining the relationship between interest rates and economic growth in different contexts. Originality/value: The core of the policy implication lay in the fact that adjusting interest rates below the threshold level of developing countries was essential to effectively promote rapid and sustainable economic growth.
Keywords: 650; Economic growth; Interest rate; Panel data; PTR model; Threshold impact